Dataset for "Serological and molecular study of Crimean-Congo hemorrhagic fever virus in cattle from selected districts in Uganda" _serology_25012021 - Balinandi, Stephen; von Brömssen, Claudia; Tumusiime, Alex; Kyondo, Jackson; Kwon, Hyesoo; Monteil, Vanessa; Mirazimi, Ali; Lutwama, Julius; Mugisha, Lawrence; Malmberg, Maja (Swedish University of Agricultural Sciences, 2021)
DATASET

This dataset presented is a summary of information about the animals and test results that are reported in the Manuscript, ‘Serological and Molecular Study of Crimean-Congo Hemorrhagic Fever Virus in cattle from selected districts in Uganda’. Below is an explanation text on some of the data variables and acronyms found in the file. A: BIODATA WORKSHEET contains information about number, code, district, sub county, parish, village and GPS location of where study samples were collected, sex of samples animal breed, age, weight, BCS, health status, rectal temperature and tick burden estimate.B: ELISA WORKSHEET contains ELISA results for 500 samples as assessed with two different assays, the In-house anti−CCHFV specific immunoglobulin g (IgG) ELISA and IDvet kit ID Screen® CCHF Double Antigen Multi-species ELISA.C: IFA AND PCR WORKSHEET contains RT-PCR performed in order to detect any CCHF viral particles in the serum samples of 37 samples. A summary of categories of samples (selected according to their individual results from the IDVet and In-house assay) and their Unique identification numbers that were tested for both IFA (Immunofluorescent assay) and PCR (Polymerase Chain Reaction). The results for each sample is indicated.

Title: Serological and molecular study of Crimean-Congo hemorrhagic fever virus in cattle from selected districts in Uganda




Journal of Virological Methods, in press 27 January 2021

https://doi.org/10.1016/j.jviromet.2021.114075

Abstract

Background: Crimean-Congo Hemorrhagic Fever (CCHF) is a severe tick-borne viral
hemorrhagic disease caused by Crimean-Congo Hemorrhagic Fever Virus (CCHFV)
that poses serious public health challenges in many parts of Africa, Europe and
Asia.

Methods: We examined 500 cattle sera samples from five districts for CCHFV antibodies
using in-house and commercially available (IDVet) ELISA, Immunofluorescent
assay (IFA) and Real-time polymerase chain reaction (RT-PCR).

Results: 500 cattle (73.8% females) were analyzed; CCHFV seropositivity was
12.6% (n = 63) and 75.0% (n = 375) with the in-house and IDVet ELISAs,
respectively. Seropositivity was associated with geographical location, increasing
age, being female, and having a higher tick burden. Twentyfour out of the 37 (64.8%)
were seropositive for CCHFV using IFA and negative for virus on RT-PCR. The IFA results were more comparable to IDVet (κcₒₑffᵢcᵢₑₙₜ
= 0.88, p =
Keywords: Medical virology; Veterinary virology; Medical and Health Sciences; Medicin och hälsovetenskap